Query-aware generation of database instances for testing database applications - Caglar, Arif Emre (University of Ottawa (Canada), 2009)
Test data preparation phase for testing database applications deals with instantiating program variables, as well as generating database instance(s) to run application queries on these instances. We first propose a method that takes a database schema, a test case representing a sequence of simple queries on a path within a transaction in a given database application, and corresponding properties associated with these queries; forms a Constraint Satisfaction Problem (CSP) by considering the interactions among the queries and the integrity constraints given by the schema; and generates, by solving this CSP, an initial database instance which satisfies the property associated with each query and is consistent with respect to the integrity constraints given in the schema. Then, we extend this method by taking a sequence of test cases containing nested queries, and generate one or more consistent database instances that satisfy the properties of queries in each test case in the given sequence of test cases. We also discuss how to integrate our method in an approach given in the literature which instantiates the input host variables of queries automatically.
Keywords: Computer Science.